1983
DOI: 10.1136/gut.24.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Copper chelation therapy in intrahepatic cholestasis of childhood.

Abstract: SUMMARY The effect of copper chelation was studied in a group of children with intrahepatic cholestasis of childhood (IHCC) and increased liver copper levels. Initial therapy was D-penicillamine (10 mg/kg/day), being replaced by triethylenetetramine dihydrochloride (20 mg/kg/day) when side-effects of D-penicillamine occurred. Eight children completed two years of copper chelation. Pruritis remained the main symptom and did not improve. Two patients developed D-penicillamine side-effects -one patient after nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This potentiating effect of vitamin E deficiency on copper toxicity may have clinical relevance in regard to chronic cholestatic liver diseases, where both secondary hepatic copper overload (37,38) and vitamin E deficiency (39,40) are common. Although it is not certain if copper overload during cholestasis is toxic to the liver (41), we have observed that reversing vitamin E deficiency in children with chronic cholestasis and secondary hepatic copper overload was associated with a decrease of fasting serum bile acid concentrations (42), suggesting that vitamin E repletion lessened hepatic injury and improved hepatic function.…”
Section: Discussionmentioning
confidence: 99%
“…This potentiating effect of vitamin E deficiency on copper toxicity may have clinical relevance in regard to chronic cholestatic liver diseases, where both secondary hepatic copper overload (37,38) and vitamin E deficiency (39,40) are common. Although it is not certain if copper overload during cholestasis is toxic to the liver (41), we have observed that reversing vitamin E deficiency in children with chronic cholestasis and secondary hepatic copper overload was associated with a decrease of fasting serum bile acid concentrations (42), suggesting that vitamin E repletion lessened hepatic injury and improved hepatic function.…”
Section: Discussionmentioning
confidence: 99%
“…The under-detection of copper deficiency could be due to limitations of screening using serum or urine samples. Although liver is the main homeostatic organ for copper and has a high copper content, copper levels in serum and urine do not correlate well with a hepatic copper concentration (19), possibly masking deficiency in the liver.…”
Section: Copper In Western Dietmentioning
confidence: 99%
“…It may be advisable to diminish copper and manganese supplements from the TPN solutions of patients with cholestatic liver disease (120). However, removal of copper by chelation therapy from the livers of children with an excessive copper burden due to cholestatic liver disease (other than Wilson's disease) has not been demonstrated to be of clinical benefit (121). Therefore, the increased retention of these elements during parenteral nutrition is of uncertain toxicity.…”
Section: Modification Of Tpnmentioning
confidence: 99%